2016
DOI: 10.2217/bmm-2016-0157
|View full text |Cite
|
Sign up to set email alerts
|

Monocyte Count-To-High-Density Lipoprotein-Cholesterol Ratio is Associated with Abdominal Aortic Aneurysm Size

Abstract: Monocyte/HDL ratio is independently associated with AAA size.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
17
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 43 publications
1
17
0
1
Order By: Relevance
“…Recognised as a recently-emerged inflammation-based marker, the monocyte count to HDL-C ratio (MHR) has been reported to be a new predictor and prognostic indicator of mortality and morbidity in many diseases [ 12 , 13 ]. The MHR has also been found to be correlated with hsCRP levels in diseases that are associated with chronic inflammation, such as cardiovascular disease [ 14 ], chronic kidney disease [ 12 ], abdominal aortic aneurysm [ 15 ], intracerebral hemorrhage [ 16 ], hypertension [ 17 ], and metabolic syndromes [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recognised as a recently-emerged inflammation-based marker, the monocyte count to HDL-C ratio (MHR) has been reported to be a new predictor and prognostic indicator of mortality and morbidity in many diseases [ 12 , 13 ]. The MHR has also been found to be correlated with hsCRP levels in diseases that are associated with chronic inflammation, such as cardiovascular disease [ 14 ], chronic kidney disease [ 12 ], abdominal aortic aneurysm [ 15 ], intracerebral hemorrhage [ 16 ], hypertension [ 17 ], and metabolic syndromes [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…In asymptomatic abdominal aortic aneurysm, a focal atherosclerotic disease, high MHR values significantly correlated with the maximum diameter of the abdominal aorta (r = 0.366) and suggested that MHR was independently associated with aneurysm size (Cagli et al, 2016) (Korkmaz et al, 2017).…”
mentioning
confidence: 99%
“…Moreover, it has been shown to be a new potential marker for predicting abdominal aortic aneurysm (AAA) size in asymptomatic patients. Çağlı et al showed that MHR was independently associated with the AAA size after dividing 120 asymptomatic AAA patients into two groups according to the MHR median value (54.3 ± 10.6 mm vs 62.0 ± 12.4 mm, P < 0.001, respectively) [26].…”
Section: Discussionmentioning
confidence: 99%